(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2017)
Artemia hatching tank of Cox’s Bazar hatchery had similar total bacterial build up (2.59 ± 0.10×107cfu/g) in the water sampled and in the shrimp post larvae (PL) sampled at stage 10 and 12 (2.37 ± 0.11×107cfu/g and 2.42 ± 0.10×107cfu/g, respectively). In MA plate, no significant differences was observed in the bacterial count of these samples. Similar result was observed for the total presumptive vibrio count in TCBS plates ranging from 3.8 ± 0.60×103cfu/g to1.62 ± 0.50×103cfu/g.Total bacterial load (7.5 ± 0.11×107) measured in the water sampled from 25 day old fry rearing pond of tilapia from Mymensingh Hatchery, was similar to that of 33 day old fry (8.6 ± .66×107). The bacterial density found in the 25 (1.6 ± 0.50×107), 28 (3.12 ± 0.14×107) and 40 day old fry (6.46 ± 1.52×106) samples was similar but significantly different from the sample of 33 day old fry and the water sample of the pond of 25 day old fry. In TCBS plate, bacterial abundance detected in the samples across all four age groups was similar (25 day old fry: 4.21 ± 3.79×103; 28 day old fry: 4.90 ± 3.50×103; 33 day old fry: 1.08 ± 0.12×103; 40 day old fry: 7.04 ± 2.08×103). In finfish hatchery of Bogra, the overall bacterial build up (2.03 ± 0.31×108) found in the samples of zeol fish fry in NA plate was significantly higher than that of the corresponding rearing pond water (2.11 ± 0.459×107) and the water of the live food rearing tank ( 8.43 ± 0.57×106). Similar to that, TCBS plates had 2.3-, and 5.09-folds higher bacterial load (1.08± 0.25×103) in the samples of fish fry than in the samples of the corresponding water samples and water samples of the live food rearing tank, respectively (4.70 ±w 1.67×102 and 2.12 ± 0.28×102). Asiat. Soc. Bangladesh, Sci. 43(1): 37-47, June 2017